A multi-functional nine channels full-spectrum light emitting diode color temperature palette - Jingjing Liang; Hui Cao; Donghua Xu; Xiaobing Lu; Feijiang Huang; Javid Atai (PLoS ONE, 2025)
A multi-functional nine-channel full-spectrum light emitting diode color temperature palette is proposed. The color temperature (CCT) of the palette can be continuously tuned at 1K interval within the range of 2500K—6500K. A high color rendering index (CRI) is achieved, with Ra > 94 and R1—R15 > 90. A fidelity index (Rf) greater than 91 is obtained, and the gamut index (Rg) within the range of 96 ≤ Rg ≤ 104 is achieved. Additionally, A chromaticity deviation (Duv) within the range of |Duv| < 0.001 is realized. The circadian effect with melanopic efficacy of luminous radiation(MELR) of 0.6 mW/lm—1.14 mW/lm and circadian action factor(CAF) of 0.289 blm/lm—0.656 blm/lm are obtained. To verify the theoretical model’s stability, the Gaussian distribution function of monochromatic LED spectrum is adjusted to induce a 5% asymmetry in integral areas, and the FWHM is offset by ±10%, simulating the non-ideal conditions in practical applications to assess the model’s robustness. The color temperature palette enables precise control and reproduction of CCT of sunlight with corresponding circadian effect, which is of positive significance for visual fields such as photography or art exhibitions and regulation of circadian rhythm.